EXPERIMENTAL INVESTIGATIONS OF DAMPERS ON BASIS OF SLOTTED CYLINDRICAL SHELLS - Бедзір, Олександр Олександрович; Шопа, Василь Михайлович; Величкович, Андрій Семенович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The results of experimental investigations of the real-life specimens of slotted shell springs of drilling tools for vibration protection are presented. The objects of research were the real-life specimens of elastic elements of drilling absorbers and laboratory models with the load bearing element in the form of slotted cylindrical shell. The process of loading the samples was implemented in the universal testing machine of the type P-50. The character of loading applied was static and quasi-static. In the process of the experiment the stress state and the radial displacements in the slotted shell, the axial compliance of elastic element, the energy dissipation in the contact system were monitored. As a result of experiments carried out the dependencies of the controlled characteristics of the contact bodies and the damper, the diagrams of deformation are built for the various physico-mechanical and geometric parameters of the system is determined.